2012
DOI: 10.1007/s10067-011-1907-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of fibromyalgia at the Maharishi Ayurveda Health Centre in Norway II—a 24-month follow-up pilot study

Abstract: Treatments offered at the Maharishi Ayurveda Health Centre in Norway are based on Maharishi Vedic Medicine (MVM). MVM is a consciousness-based revival by Maharishi Mahesh Yogi, the founder of the Transcendental Meditation (TM) program of the ancient Ayurvedic medicine tradition in India. To extend from 6 to 24 months, a pilot study of the effects of the treatment program at the Health Centre on fibromyalgia. Retesting 2 years after a clinical trial. In this intention to treat study, 31 women with a diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…A small uncontrolled study in 28 patients found an Ayurvedic program, also focusing on nutrition and mind-boy techniques, to be effective with a lasting effect up to 24 months [36]. However, the treatment was not compared to another intervention, thus selection bias and unspecific effects were most likely contributing factors to the effect.…”
Section: Discussionmentioning
confidence: 99%
“…A small uncontrolled study in 28 patients found an Ayurvedic program, also focusing on nutrition and mind-boy techniques, to be effective with a lasting effect up to 24 months [36]. However, the treatment was not compared to another intervention, thus selection bias and unspecific effects were most likely contributing factors to the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, Ayurveda is one of the fastest growing CAM systems [17, 18]. First and small clinical trials have hinted at a possible effectiveness of Ayurveda in the treatment of FMS, yet the available data is still too weak to draw definite conclusions as these trials were uncontrolled [29–32] and included meditation as part of the Ayurveda-labeled treatment [29, 30]. Several Ayurveda trials have been done on other disease entities from the field of rheumatology, for example, on rheumatoid arthritis and osteoarthritis; here the quality of data seems to be clearly better (e.g., [17, 24, 25]).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience and preliminary evidence from uncontrolled prospective studies suggest that a CIM approach focusing on Ayurveda may help to decrease symptoms of FMS [29–32]. However, it would be useful to know how such an approach would act, if compared with CoM FMS treatment, as established in specialized hospital units of rheumatology or pain medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Es liegen Veröffentlichungen vor, in denen die Ayurveda-Medizin bei FMS untersucht wurde [8,9] Zur Wirksamkeit ayurvedischer Therapieverfahren bei Erkrankungen mit Schmerzkomponenten liegen zudem zahlreiche weitere Studien vor [10].…”
Section: Zkm Praxis Ayurvedaunclassified
“…Selbst wenn aktuelle Leitlinien zum FMS Massagen allgemein als negativ bewerten, so zeigt sich dieser im Ayurveda hochspezialisierte Therapiezweig als wirksam [9], sofern er nach genauer Indikationsstellung individualisiert und in geeigneter Kombination angewendet wird. Ohne den Wirkmechanismus an dieser Stelle genauer beleuchten zu wollen, werden zudem regelmäßige nasale Anwendungen von pflanzlichen Substanzen in einem fettbasierten Medium verabreicht.…”
Section: äUßere Anwendungenunclassified